Bedtime Electronic Media Use and Sleep in Children with Autism Spectrum Disorder. Issue 7 (September 2016) - Mazurek, Micah O.; Engelhardt, Christopher R.; Hilgard, Joseph; Sohl, Kristin
ABSTRACT: Objectives: The purpose of this study was to better understand the use of screen-based media at bedtime among children with autism spectrum disorder (ASD). The study specifically examined whether the presence of media devices in the child's bedroom, the use of media as part of the bedtime routine, and exposure to media with violent content just before bedtime were associated with sleep difficulties. Methods: Parents of 101 children with ASD completed questionnaires assessing their children's sleep habits, bedroom media access (including television, video game devices, and computers), and patterns of nighttime media use (including timing of media exposure and violent media content). Results: Children with ASD who used media as part of the bedtime routine showed significantly greater sleep onset latency than those who did not (39.8 vs 16.0 minutes). Similarly, children who were exposed to media with violent content within the 30-minute period before bedtime experienced significantly greater sleep onset delays and shorter overall sleep duration. In contrast, the mere presence of bedroom media was not associated with either sleep onset latency or sleep duration. Conclusion: Overall, these findings indicate that incorporating television and video games into the bedtime routine is associated with sleep onset difficulties among children with ASD. Exposure to violent media before bed is also associated with poor sleep. Families of children with ASD should be encouraged to regulate and monitor the timing and content of television and video game use, whether or not such devices are physically present in the child's bedroom.